Porin Expression Profiles in Haemaphysalis longicornis Infected With Babesia microti - Zheng, Weiqing; Umemiya-Shirafuji, Rika; Zhang, Qian; Okado, Kiyoshi; Adjou Moumouni, Paul Franck; Suzuki, Hiroshi; Chen, Haiying; Liu, Mingming; Xuan, Xuenan (Frontiers in Physiology, 2020)
The porin gene is widely disseminated in various organisms and has a pivotal role in the regulation of pathogen infection in blood-sucking arthropods. However, to date, information on the porin gene from the Haemaphysalis longicornis tick, an important vector of human and animal diseases, remains unknown. In this study, we identified the porin gene from H. longicornis and evaluated its expression levels in Babesia microti-infected and -uninfected H. longicornis ticks at developmental stages. We also analyzed porin functions in relation to both tick blood feeding and Babesia infection and the relationship between porin and porin-related apoptosis genes such as B-cell lymphoma (Bcl), cytochrome complex (Cytc), caspase 2 (Cas2), and caspase 8 (Cas8). The coding nucleotide sequence of H. longicornis porin cDNA was found to be 849 bp in length and encoded 282 amino acids. Domain analysis showed the protein to contain six determinants of voltage gating and two polypeptide binding sites. Porin mRNA levels were not significantly different between one-day-laid and seven-day-laid eggs. In the nymphal stage, higher porin expression levels were found in unfed, 12-h-partially-fed (12hPF), 1-day-partially-fed (1dPF), 2dPF nymphs and nymphs at 0 day post engorgement (0dAE) versus nymphs at 2dAE. Cytc and Cas2 mRNA levels were higher in 2dPF nymphs in contrast to nymphs at 2dAE. Porin expression levels appeared to be higher in the infected versus uninfected nymphs during blood feeding except at 1dPF and 0–1dAE. Especially, the highest B. microti burden negatively affected porin mRNA levels in both nymphs and female adults. Porin knockdown affected body weight and Babesia infection levels and significantly downregulated the expression levels of Cytc and Bcl in H. longicornis female ticks. In addition, this study showed that infection levels of the B. microti Gray strain in nymphal and female H. longicornis peaked at or around engorgement from blood feeding to post engorgement. Taken together, the research conducted in this study suggests that H. longicornis porin might interfere with blood feeding and B. microti infection.